PENGARUH KOMPENSASI, PELATIHAN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN MARKETING - Citra Andriani; Onsardi Onsardi (UM. Bengkulu, 2020)
This study entitled the effect of Compensation, Job Training and Job Satisfaction on Marketing Employee Performance at PT. Agung Toyota Bengkulu. The formulation of the problem in this study was whether the effect of Compensation, Job Training and Job Satisfaction on Marketing Employee Performance at PT. Agung Toyota Bengkulu. The purpose of this study was to determine whether the influence of Compensation, Job Training and Job Satisfaction on Marketing Employee Performance at PT. Agung Toyota Bengkulu. This research was conducted on marketing employees of PT. Agung Toyota Bengkulu. While the time of this study was conducted for 11 days, namely on 18 January to 28 January 2020. The population of this study were employees at PT. Agung Toyota Bengkulu, while the sample of this research is marketing employees of PT. Agung Toyota Bengkulu, amounting to 97 people. This means that the sample material uses quantitative methods. With research test data analysis techniques, the results of the study can be concluded that the respondents' perceptions about Compensation (X1), Job Training (X2) and Job Satisfaction (X3) affect the Performance of Marketing Employees (Y) with the results of multiple linear regression obtained the following equation: Y = 1.734 + 0.378 (X1) + 0.570 (X2) + 0.328 (X3) and the coefficient of determination of R2 = 0.802 or approximately (802%) through hypothesis testing simultaneously (simultaneously) and individually (partial) in this study by using the f test and t test, Compensation (X1), Job Training (X2) and Job Satisfaction (X3), = 0.000, it means that values <0.05 show together and have significant influence. Keywords: Compensation, Job Training and Job Satisfaction Employee Performance